Reports from the Dorsland - Merwe, PJ van der (African Sun Media, 2020)
'Shortly after his appointment as lecturer in Stellenbosch, historian PJ van der Merwe turned his attention to the Northwest. In those days the region was mostly unknown to people outside this part of the world. Like today, there was uncertainty then about the boundaries of this region and its sub-regions ... Berigte uit die Dorsland, compiled by Van der Merwe's daughter, Margaretha Schaefer, contains more than 200 of his magazine and newspaper articles. The articles, based on interviews and observations, offer a wealth of important information that he gathered during two extensive visits to the Northwest and surrounding regions ... He realised, long before most historians, that a personal interview with someone, who has had a particular experience, was an important historical source. But, it was essential to test the evidence and verify it with that of other people. The articles in Die Burger, Die Huisgenoot, Die Landbouweekblad and Sarie Marais are accompanied by excellent photographs taken by Van der Merwe.' HERMANN GILIOMEE